2015
DOI: 10.1093/mnras/stv2369
|View full text |Cite
|
Sign up to set email alerts
|

Nebular spectra of pair-instability supernovae

Abstract: If very massive stars (M 100 M ⊙ ) can form and avoid too strong mass loss during their evolution, they are predicted to explode as pair-instability supernovae (PISNe). One critical test for candidate events is whether their nucleosynthesis yields and internal ejecta structure, being revealed through nebular-phase spectra at t 1 yr, match those of model predictions. Here we compute theoretical spectra based on model PISN ejecta at 1-3 years post-explosion to allow quantitative comparison with observations. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
71
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 94 publications
5
71
5
Order By: Relevance
“…With the multi-epoch coverage of SN 2015bn (and LSQ14an) we see significantly more rapid decline than 56 Co decay (see also (Nicholl et al 2016b) and Inserra et al, in prep.). This cannot be achieved in PISN models, which have complete gamma-trapping for at least 500d (Jerkstrand et al 2016). Some transfer to the nearinfrared may occur, but the NIR observations here indicate that this is a weak process.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…With the multi-epoch coverage of SN 2015bn (and LSQ14an) we see significantly more rapid decline than 56 Co decay (see also (Nicholl et al 2016b) and Inserra et al, in prep.). This cannot be achieved in PISN models, which have complete gamma-trapping for at least 500d (Jerkstrand et al 2016). Some transfer to the nearinfrared may occur, but the NIR observations here indicate that this is a weak process.…”
Section: Discussionmentioning
confidence: 58%
“…While there is some debate whether broad-lined Type Ic SNe are powered by 56 Ni or a central engine, existing 56 Ni models are successful enough to maintain this as the standard picture. Thus, "scaled-up" 56 Ni powered explosion models must still be pursued for SLSNe, even though the PISN variant of these have not compared well to observations so far (Dessart et al 2013;Jerkstrand et al 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Calculated optical spectra at the nebular phase, based on pair-instability supernova (PISN) models, seem to show a relatively weak [O I] 6300 doublet (Jerkstrand et al 2016). At face value, this could be considered to be supporting evidence for a PISN or PPISN model for these events.…”
Section: Weak [O I] 6300 Doublet Emissionmentioning
confidence: 86%
“…First, the ejecta of our three events may have lower oxygen masses, and perhaps also lower progenitor masses than that of SN2015bn and SN2007bi. The recent modeling of the nebular spectra of SN2015bn and SN2007bi by Jerkstrand et al (2016) …”
Section: Weak [O I] 6300 Doublet Emissionmentioning
confidence: 99%
“…Among the SLSNe I, we denote a small number of events (three) as belonging to the subclass of long-lived "R"-types, which show exponentially declining late-time light curves consistent with radioactive decay and which have been suggested to be examples of PISNe (Gal-Yam et al 2009;Gal-Yam 2012), although this interpretation is contested by other authors (e.g., Dessart et al 2012;Nicholl et al 2013;Jerkstrand et al 2016). We will generally refer to them as Type "I-R." With only three events, we do not have sufficient sample size to perform a statistically robust comparison between the host properties of these events and the more rapidly declining SNeI, but as we observe no strong distinction between the host properties of these events and other SLSNe I in our sample (and other authors have reported similar results; e.g., Lunnan et al 2014;Leloudas et al 2015), we will generally treat all SLSNe I together in our analysis regardless of their light-curve properties.…”
Section: Subclassification Of Slsnementioning
confidence: 99%